ANALISIS VARIABEL YANG MEMPENGARUHI JUMLAH PENGANGGURAN TERDIDIK DI INDONESIA - Mada, Muhammad; Ashar, Khusnul (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
The growth of a large population is not matched by the spread evenly and lack of labor market led to a reduction in the chance of getting a job. This leads to insecurity and did not rule out the emergence of crime. Besides the prolonged economic crisis also worsened the problems facing the government in developing the field of employment. Unemployment in Indonesia experienced by almost the whole of society with different strata of each level of education. The problem in this research is how economic factors affect the level of unemployment in Indonesia. In addition, factors that influence the success of one's education in obtaining a job or not getting work is a phenomenon in society in Indonesia later by the authors defined as a formulation problem in this study. This study uses several variables that allow in this study include level of education, age of the workforce, as well as economic factors were then analyzed quantitatively. Data analysis tool in this study with correlation used by the author as a step to address the problem in this study. The purpose of this study was to determine the factors that affect the educated unemployment in Indonesia. The benefits of this research that this study are expected to provide a good education in general and specifically in economics about the factors affecting unemployment in Indonesia, especially in Kalanga educated. In addition this study is expected to be a reference for further research and as a reference to the central government and regency / municipal government in determining policies for many people to Indonesia more dignified, advanced, and prosperous. Keywords: Population, Employment, UnemploymentJEL Classification: J62, J64